What Drives the Gender Wage Gap? Examining the Roles of Sorting, Productivity Differences, Bargaining, and Discrimination - Sin, Isabelle; Stillman, Steven; Fabling, Richard (The Review of Economics and Statistics, 2022)
As in other OECD countries, women in New Zealand earn substantially less than men with similar observable characteristics. In this paper, we use fifteen years of linked employer-employee data to examine different explanations for this gender wage gap. We find an overall gender wage gap between 20% and 28%, of which gender differences in sorting across occupations explain 9%, across industries 16% to 19%, and across firms 5% to 9%, respectively. The remaining within-firm gender wage gap is still between 13% and 17%. Around 5 percentage points of this are explained by women being less willing to bargain or less successful at bargaining to capture firm-specific rents. Gender differences in productivity also explain at most 4.5 percentage points of this remaining gap. These results suggest that taste discrimination is also important for explaining why women are paid less than their relative contribution to firm output. Across-industry and over-time variation in the gender wage-productivity gap further support this conclusion.